Evaluating the factors on employee turnover intention at Singapore Telecommunication (SingTel), Melaka / Eirma Sabtu - Sabtu, Eirma (2019)
The purpose of this study was to evaluate the factors on employee turnover intention at SingTel, Melaka. Job satisfaction can be influenced by a person's ability to complete the required tasks, the level of communication in an organization, and the way the management treats employees. Measuring human resource practice can be challenging, as the definition of satisfaction can be different for different people. This dissertation evaluated factors on employee intention with job satisfaction. The research design was a cross-sectional study, where a survey was conducted at Singapore Telecommunication (SingTel) Melaka Branch. Hence, this study is an institutional case study. The statements in the questionnaire measured four independent variables, which are Performance Appraisal, Training and Development, Compensation and Benefits, and Career Development. The population sample size was 140 (n==140), with a 100% response rate. The data collected were analyzed using the software, Statistical Package for the Social Sciences (SPSS) version 22. The questionnaire was distributed through the social media platform, WhatsApp, as well as through personal delivery. Therefore, based on the correlation analysis, there is a significant relationship between Employee Turnover Intention with Performance Appraisal, Training and Development., Compensation and Benefits, and Career Development. The implications of the study would enable SingTel managers to improve job satisfaction through aligned human resource practices.